1965
DOI: 10.1002/ajpa.1330230129
|View full text |Cite
|
Sign up to set email alerts
|

ABO blood groups and hemoglobin variants among Nubians, Egypt, U.A.R.

Abstract: Three hundred and fifty-six Nub i ans of Upper E gypt w er e te st ed for h emogl obin v arian ts a nd ABO blood groups. N o h emogl obin varian ts were detected . ABO all el e frequ encie s f or the Konouz a r e : A 19 .31 , B 11. 08 , 0 69 .59; f or th e Arabs -A 22.02, B 9.64, 0 68.33 ; an d for th e F ediky aee -A 24.46, B 9 .5 4 , 0 65.98. A. Y . AWNY, KARIM A. KAMEL AND KIRK C. HO ERM AN N f'. ;:0 C> :2' 5 §' " C> ] e o r-, C"?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1967
1967
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…The first case of SCA in Egypt was reported in 1951 by Abbasy88. Other abnormalities of haemoglobin were also identified89. Since then, several studies have been carried out and shown that, in Egypt, β-thalassaemia is the most common type with a carrier rate varying from 5.3-9 per cent and a gene frequency of 0.03.…”
Section: Frequency and Distribution Of Sickle Cell Gene Among Arabsmentioning
confidence: 99%
“…The first case of SCA in Egypt was reported in 1951 by Abbasy88. Other abnormalities of haemoglobin were also identified89. Since then, several studies have been carried out and shown that, in Egypt, β-thalassaemia is the most common type with a carrier rate varying from 5.3-9 per cent and a gene frequency of 0.03.…”
Section: Frequency and Distribution Of Sickle Cell Gene Among Arabsmentioning
confidence: 99%
“…It varies from race to race, one country to another and even in different regions of a country. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] This spectrum of difference may be attributed to genetic factors and natural selection which is affected mainly by traditions and habits namely exogamy and endogamy. Global frequency pattern of the type B blood allele is highest in central Asia and in few pockets of Africa but lowest in the America and Australia.…”
Section: Introductionmentioning
confidence: 99%
“…The scarcity or absence of Hb H in Egypt is substantiated by a similar finding in surveys and studies which covered the majority of Egyptian territories (Kamel et al, 1960;Awny, Kamel, and Hoerman, 1965;Kamel, 1968;Azim et al, 1974;Ibrahim et al, 1974;Selim et al, 1974) as well as in neighbouring Libya (Kamel etal, 1975).…”
Section: Discussionmentioning
confidence: 64%